The Role of Ultrasound as a Diagnostic and Therapeutic Tool in Experimental Animal Models of Stroke: A Review - Mari Carmen Gómez-de Frutos; Fernando Laso-García; Iván García-Suárez; Luke Diekhorst; Laura Otero-Ortega; María Alonso de Leciñana; Blanca Fuentes; Dolores Piniella; Gerardo Ruiz-Ares; Exuperio Díez-Tejedor; María Gutiérrez-Fernández (Biomedicines, 2021)
Ultrasound is a noninvasive technique that provides real-time imaging with excellent resolution, and several studies demonstrated the potential of ultrasound in acute ischemic stroke monitoring. However, only a few studies were performed using animal models, of which many showed ultrasound to be a safe and effective tool also in therapeutic applications. The full potential of ultrasound application in experimental stroke is yet to be explored to further determine the limitations of this technique and to ensure the accuracy of translational research. This review covers the current status of ultrasound applied to monitoring and treatment in experimental animal models of stroke and examines the safety, limitations, and future perspectives.